2016
DOI: 10.1177/1079063216649592
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Validity of Three Measures of Sexual Sadism: Value of a Dimensional Measure

Abstract: Sexual sadism can be described as the sexual pleasure produced by acts of cruelty and bodily punishment. The most common method for evaluating sexual sadism is clinical evaluation, that is, evaluation based on the diagnostic criteria of nosological instruments such as the Diagnostic and Statistical Manual of Mental Disorders ( DSM) or the International Classification of Diseases (ICD). It is also possible to evaluate sadistic sexual preferences by phallometry, which provides a physiological measure of sexual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The composite score of the Part 1 items was shown to have excellent interrater agreement, with an intraclass correlation coefficient (ICC) of [2, 5] (i.e., average measure, absolute agreement ϭ .91) in a sample of 20 cases assessed by five raters (Mokros et al, 2014). The Part 1 sum score showed a moderate to substantial correlation with clinical diagnoses of sadism (r pc ϭ .55 according to Eher et al, 2016; r pc ϭ .46 according to Longpré, Proulx, & Brouillette-Alarie, 2018; area under the curve ϭ .87 according to Mauzaite, Sauter, Seewald, & Dahle, 2017). Furthermore, the Part 1 sum score was strongly correlated (r ϭ .66) with the Massachusetts Treatment Center Sadism Scale (Longpré, Guay, & Knight, 2017).…”
Section: Apa Nlmmentioning
confidence: 97%
See 1 more Smart Citation
“…The composite score of the Part 1 items was shown to have excellent interrater agreement, with an intraclass correlation coefficient (ICC) of [2, 5] (i.e., average measure, absolute agreement ϭ .91) in a sample of 20 cases assessed by five raters (Mokros et al, 2014). The Part 1 sum score showed a moderate to substantial correlation with clinical diagnoses of sadism (r pc ϭ .55 according to Eher et al, 2016; r pc ϭ .46 according to Longpré, Proulx, & Brouillette-Alarie, 2018; area under the curve ϭ .87 according to Mauzaite, Sauter, Seewald, & Dahle, 2017). Furthermore, the Part 1 sum score was strongly correlated (r ϭ .66) with the Massachusetts Treatment Center Sadism Scale (Longpré, Guay, & Knight, 2017).…”
Section: Apa Nlmmentioning
confidence: 97%
“…Moreover, testing the criterion validity of instruments like the SeSaS with clinical diagnoses of sadism is a somewhat suboptimal strategy given the concerns about the reliability of clinician judgments for this diagnosis (Nitschke et al, 2013). Therefore, physiological measurement may provide further evidence of criterion validity (see, e.g., Seto, Lalumière, Harris, & Chivers, 2012, for a useful stimulus set) even though extant results using phallometry yielded nil correlations (Longpré et al, 2018).…”
mentioning
confidence: 99%
“…Several authors have suggested that a dimensional approach that indicates the severity of sexual sadism, rather than the presence or absence of the disorder, could be a viable alternative to the current categorical system provided by diagnostic manuals (Berner, Berger, & Hill, 2003; Bradley, Shedler, & Westen, 2006; Longpré et al, 2018; Marshall & Kennedy, 2003; Mokros et al, 2014; Nitschke et al, 2013). Using indices from crime scenes, sexual sadism could be more behaviorally operationalized (Kingston et al, 2010; Marshall & Kennedy, 2003).…”
Section: Sexual Sadism Diagnosismentioning
confidence: 99%
“…For this reason, researchers have begun developing psychometric assessment instruments for sexual sadism composed of behavioral indicators that can be rated based on crime-scene information (e.g., Nitschke, Osterheider, & Mokros, 2009). However, research on the psychometric properties of such tools is still scarce and, therefore, little is known about their utility in the forensic context (Longpré, Proulx, & Brouillette-Alarie, 2018). The present study cross validates the Sexual Sadism Scale (SeSaS; Nitschke et al, 2009) within a sample of male sex offenders in Switzerland.…”
mentioning
confidence: 99%
“…However, the wider literature indicates no differences in penile responses between sadists and non-sadists. The reason for this could be that phallometric rape scenarios might be better suited to assess sexually aggressive behaviors that are not overtly sadistic, or because phallometry does not tap into idiosyncratic sadistic fantasies (Longpré, Proulx, & Brouillette-Alarie, 2016). Therefore, while the effects of anger on not overtly sadistic non-consenting sexual arousal can be shown, at the moment it is difficult to measure the possible interaction between anger and sadistic behavior.…”
Section: Introductionmentioning
confidence: 99%